Orçamento participativo em municípios predominantemente rurais - Hemerson Luiz Pase (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2003)
The work studies the possibilities for implementation of innovative ways of administration ofthe public resources with the citizens participation, just as the participatory budget , inmunicipal districts predominantly rural, considering the potentiality of these innovations forthe rural development. The preliminary results indicate that, nevertheless the disposition(programmaticaly assumed or not) of the rulers in giving important spaces of power to thecitizens´ group, serious difficulties exist predominantly of implanting with success theparticipatory budget in municipal districts rural. These difficulties are due to historicalrelationships of clientelism and patrimonialism among citizens, state bureaucracy and cannotpublic, and mainly the impossibility of the municipal administration in providing a minimum of resources (important) to be indeed managed for the citizens.